Lithic Materials and Paleolithic Societies 2009
DOI: 10.1002/9781444311976.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction, Recycling, and Raw Material Procurement in Western Arnhem Land, Australia

Abstract: Complex lithic assemblage variation in Arnhem Land, Australia, was initially explained by suggestions that multiple cultural groups had co-existed or that a single group had used different toolkits as they moved seasonally to exploit temporary resources. These models have proved untenable and differences in assemblage composition across the landscape are now explained in terms of procurement economics: as knappers rationed, recycled, and substituted artifacts in response to the varying cost of obtaining replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…In this respect, ethnoarchaeological studies have demonstrated that projectile points are frequently used for non-projectile purposes. Perhaps the closest ethnographic analog with MSA points are the leilira blades, or "men's knives," documented among aboriginal groups in the northern, central and western arid regions of Australia (Binford 1986;Binford and O'Connell 1984;Hayden 1979;Hiscock 1994Hiscock , 2009McCall 2012;see Shea 1997 for a discussion of the similarity of leiliras with Middle Paleolithic points). As Hayden (1979) details, leiliras may be hafted as either knives or spear points and are frequently shifted from one purpose to another.…”
Section: Research On Sb Bifacial Point Functions and Tool Designsmentioning
confidence: 97%
See 3 more Smart Citations
“…In this respect, ethnoarchaeological studies have demonstrated that projectile points are frequently used for non-projectile purposes. Perhaps the closest ethnographic analog with MSA points are the leilira blades, or "men's knives," documented among aboriginal groups in the northern, central and western arid regions of Australia (Binford 1986;Binford and O'Connell 1984;Hayden 1979;Hiscock 1994Hiscock , 2009McCall 2012;see Shea 1997 for a discussion of the similarity of leiliras with Middle Paleolithic points). As Hayden (1979) details, leiliras may be hafted as either knives or spear points and are frequently shifted from one purpose to another.…”
Section: Research On Sb Bifacial Point Functions and Tool Designsmentioning
confidence: 97%
“…Arising at first within North American archaeological circles, a view developed of biface technology as multifunctional, versatile (i.e., capable of being retouched into a number of separate final forms), and efficient in terms of raw material economy (Hiscock 1994(Hiscock , 2009Kelly 1988;Kelly and Todd 1988;Jeske 1989;Odell 1996;Parry and Kelly 1987;Shott 2007;Whittaker 1994). By virtue of these features (and others), bifaces were linked with frequent and/or long-distance residential mobility and have been conceptualized in terms of the curation construct (see Odell 1996 for a review of this line of research).…”
Section: Research On Sb Bifacial Point Functions and Tool Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a number of publications Hiscock (1996Hiscock ( , 1999Hiscock ( , 2009Hiscock et al 1992) reassessed the proposed lithics sequences and settlement patterns for the region. In 1992…”
Section: Re-interpretation Of the Lithics Sequence And Settlement Patmentioning
confidence: 99%